Morfogénesis de los gametofitos de especies mexicanas de Pleopeltis (Polypodiaceae, subfamilia Pleopeltoideae) - Reyes Jaramillo, Irma (2003)
the development and morphology of the gametophytes of seven species of ferns from genus Pleopeltis are described and compared. The spore germination is Vittaria-type in P. astrolepis, P. crassinervata, P. macrocarpa, P. polylepis and P. revoluta. For P. angusta and P. mexicana it was proposed a new germination pattern is Pleopeltis-type. The prothallial development is Drynaria-type in P. astrolepis, P. crassinervata, P. macrocarpa, P. polylepis and P. revoluta and Ceratopteris-type for P. angusta and P. mexicana. The gametangia are typical of the leptosporangiate ferns, sporophytes after six and a half months in culture did not appeared.